In vivo tracking of toxic diesel particulate matter in mice using radiolabeling and nuclear imaging. (February 2023) - Park, Jung Eun; Lee, Jun Young; Chae, Jungho; Min, Chang Ho; Shin, Hee Soon; Lee, So-Young; Lee, Jae Young; Park, Jeong Hoon; Jeon, Jongho
Abstract: Exposure to diesel particulate matter (DPM) is associated with several adverse health effects, including severe respiratory diseases. Quantitative analysis of DPM in vivo can provide important information on the behavior of harmful chemicals, as well as their toxicological impacts in living subjects. This study presents whole-body images and tissue distributions of DPM in animal models, using molecular imaging and radiolabeling techniques. The self-assembly of the 89 Zr-labeled pyrene analog with a suspension of DPM efficiently produced 89 Zr-incorporated DPM ( 89 Zr-DPM). Positron emission tomography images were obtained for mice exposed to 89 Zr-DPM via three administration routes: intratracheal, oral, and intravenous injection. DPM was largely distributed in the lungs and only slowly cleared after 7 days in mice exposed via the intratracheal route. In addition, a portion of 89 Zr-DPM was translocated to other organs, such as the heart, spleen, and liver. Uptake values in these organs were also noticeable following exposure via the intravenous route. In contrast, most of the orally administered DPM was excreted quickly within a day. These results suggest that continuous inhalation exposure to DPM causes serious lung damage and may cause toxic effects in the extrapulmonary organs. Graphical abstract: Image 1 Highlights: A 89 Zr-labeling method was used for tracing diesel particulate matter (DPM) in mice. 89 Zr-incorporated DPM was administered in mice via three different routes. When exposed via the intratracheal route, DPM was highly distributed in the lungs and excreted slowly. Uptake in some organs such as spleen and heart were evident following intravenous exposure. Most of the orally administered diesel particulates were cleared quickly in a day.